Automating co-curricular management: an NFC-based system for streamlining student engagement at IIUM - Mahmod Attar Bashi, Zainab Senan; Kamarudin, Kay Aiman Fitri; Mohammad Rafaii, Ikmal Ikhwan; Sakka, Oula; Mohd Aman, Azana Hafizah (PENERBIT UniMAP, 2026)
In today’s educational systems, academic excellence alone is insufficient for a holistic development approach. Equally important is the active participation of students in co-curricular activities, which contribute significantly to their overall growth and skill development. Managing student co-curricular activities without an automated system often leads to significant administrative burdens, data inaccuracies, and inefficient use of resources due to reliance on manual processes like paper-based sign-ins and spreadsheets. Furthermore, the accurate recording of these activities is necessary not only for validating student participation and awarding credits but also for providing data-driven insights into engagement patterns and the overall effectiveness of university programs. To improve the tracking of student involvement in co-curricular activities, this study proposes integrating Near-field Communication (NFC) technology into IIUM's existing Starpoint system, thereby addressing its current operational challenges. The current system at IIUM faces several challenges, including delays in record updates, data loss, and human errors. These issues not only affect the accurate tracking of student engagement but also affect the timely acknowledgment of their efforts. The proposed NFC-based system seeks to address these problems by employing NFC tags, transceivers, readers, and microcontrollers to automatically and instantaneously collect and update Starpoint data. The system also introduces a Starpoint bank that allows students to collect Starpoints and use them as a form of currency within the university to gain various incentives including access to special events, or priority in certain university services. The paper reviews previous works that have explored the use of NFC technology in educational settings, highlighting their successes and limitations. It then explains the proposed design, implementation, and evaluation of the system. The results from the pilot project indicate significant improvements in the speed and reliability of recording student participation.